Impact of Perceived Quality of E-Health Services on Patient Behavioral Intention to Use E-Health Services: A Moderating Role of Knowledge of E-Health Management - Alshammari, Tai Abdulrahman; Alshammary, Khalid Mhasan; Alshammari, Fahad Maiyah (Journal of Economics and Behavioral Studies, 2022)
The objective of this study is to investigate the impact of perceived quality of e-health and the perceived usefulness of behavioral intention to use e-health services with moderating role of knowledge on e-health. A quantitative research approach was applied to examine the proposed relationships between variables of the model. A cross-sectional method was used to gather the data from Saudi patients with the help of a self-administrative survey questionnaire. Findings illustrated that IQ, system quality, and perceived usefulness have a significant and positive impact on the behavioral intention to use e-health services of Saudi patients. Moreover, results show that knowledge of e-health significantly moderates the relationship between perceived quality of e-health and perceived usefulness with the patients’ intention to use e-health services. This study enriches the body of knowledge regarding e-health usage, patient intention to use services of e-health, and literacy regarding e-health. The findings of the present study improve the understanding of health care executives regarding the use of e-health services intention and how this intention can be improved.